Ethics and Technology Assessment: A Participatory Approach - Cotton, Matthew. author. aut Link
XII, 172 p. 8 illus.
Keywords: Whether it is nuclear power, geo-engineering or genetically modified foods, the development of new technologies can be fraught with complex ethical challenges and political controversy which defy simple resolution. In the past two decades there has been a shift towards processes of Participatory Technology Assessment designed to build channels of two-way communication between technical specialists and non-expert citizens, and to incorporate multiple stakeholder perspectives in the governance of contentious technology programmes. This participatory turn has spurred a need for new tools and techniques to encourage group deliberation and capture public values, moral and choices. This book specifically examines the ethical dimensions of controversial technologies, and discusses how these can be evaluated in a philosophically robust manner when the ones doing the deliberating are not ethicists, legal or technical experts. Grounded in philosophical pragmatism and drawing upon empirical work in partnership with citizen-stakeholders, this book presents a model called “Reflective Ethical Mapping” - a new meta-ethical framework and toolbox of techniques to facilitate citizen engagement with technology ethics.